Jews, Christians, and the abode of Islam modern scholarship, medieval realities - Lassner, Jacob (The University Of Chicago Press, 2012)
Lassner shows just what medieval Muslims meant when they spoke of tolerance, and how that abstract concept played out at different times and places in the real world of Christian and Jewish communities under Islamic rule. Finally, he considers what a more informed picture of the relationship among the Abrahamic faiths in the medieval Islamic world might mean for modern scholarship on medieval Islamic civilization and, not the least, for the highly contentious global environment of today.